OPAVIVARÁ! Modos de vida na arte contemporânea - Campos, Livia Fernandes; Grando, Angela (Farol, 2022)
OPAVIVARÁ! is an art collective from Rio de Janeiro that since 2005 has been carrying out actions in public spaces and cultural institutions. Based on your proposals, OPAVIVARÁ! often shows social and political conflicts, without apparently wanting to present a lasting artistic project, an art mode hostage to a universal ideology. Their actions seem to propose alternative ways of interaction between individuals and between them and the urban space. In this article we will investigate how their proposals are structured, and, for that, we will use ideas based on the work of Nicolas Bourriaud and Jacques Rancière, among others authors